Inkonsistensi Aturan Pertanggungjawaban Pidana Pencucian Uang Oleh Korporasi: Perlukah Reformulasi? - Hanna Rosyidah; Bayu Satya Ndharma; Naya Aulia Zulfa (CV Rewang Rencang, 2021)
Money laundering is a transnational crime that must get serious attention from policymakers. This crime is regulated in provisions outside the Criminal Code, namely in Law Number 8 of 2010 concerning the Crime of Money Laundering. In the Act, there has been an expansion of the meaning of the subject of criminal law which is not limited only to humans, but also to corporations. In verdict No. 84/Pid.B/2018/PN.Dpk, in the First Travel case, the Panel of Judges gave punishment to the controlling personnel of the corporation, but not to the corporation. So this raises the question of whether there has been an inconsistency in the application of corporate responsibility because in its implementation the criminal responsibility for money laundering is still delegated to the controlling personnel of the corporation. This resulted in the corporation as a subject of criminal law cannot be fully responsible for the crime committed. By using a normative juridical research method as well as a statutory approach, a conceptual approach, a case approach, and a comparative approach. This study aims to determine how far corporate responsibility is according to Law Number 8 of 2010. The results of this study indicate that there are still doubts by law enforcement officers in deciding cases of money laundering crimes by PT. First Anugerah Karya Wisata so that it has not fully delegated responsibility to corporations as well as in Law Number 8 of 2010 in which the formulation of the article still has many weaknesses so that the law does not provide uniformity in imposing criminal sanctions against corporations.